Redescription of a little known assassin bug Caunus noctulus Hsiao (Hemiptera: Reduviidae: Stenopodainae), with special reference to its sexual dimorphism - Cao, Liangming; Zhao, Ping; Cai, Wanzhi (Zootaxa, 2011)
The stenopodaine assassin bug, Caunus noctulus Hsiao, has a distinct sexual dimorphism. In this paper the morphological characters of this species are redescribed based on the holotype and other materials. Illustrations of habitus, head, pronotum, and other structures are provided to facilitate recognition of this little known reduviid.